2014
DOI: 10.2319/112113-856.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of repeated oral hygiene motivation and type of toothbrush on orthodontic patients:A blind randomized clinical trial

Abstract: Objective: To investigate the effects on plaque index (PI) scores of manual or electric toothbrush with or without repeated oral hygiene instructions (OHI) and motivation on patients wearing fixed orthodontic appliances. Materials and Methods: One month after the orthodontic fixed appliance bonding on both arches, 60 patients were randomly assigned to four groups; groups E 1 (n 5 15) and E 2 (n 5 15) received a powered rotating-oscillating toothbrush, and groups M 1 (n 5 15) and M 2 (n 5 15) received a manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 25 publications
1
51
1
6
Order By: Relevance
“…Further investigations should analyze the effects of repeated motivation on PI score trends during the entire duration of orthodontic treatment in order to provide an orthodontic hygiene protocol [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations should analyze the effects of repeated motivation on PI score trends during the entire duration of orthodontic treatment in order to provide an orthodontic hygiene protocol [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Optimal oral hygiene requires thorough and clear professional instructions, adequate tools, and patient motivation, which is an essential factor to obtain compliance [2, 3]. A systematic review of randomized controlled trials conducted by Gao and colleagues [4] showed varied success in using motivational approaches, which are potentially more useful to achieve behavioral changes than conventional health education, focusing on disseminating information and giving normative advice.…”
Section: Introductionmentioning
confidence: 99%
“…, 10 , 26 , 27 Longitudinal studies should take into consideration these factors and take a deeper look at the relationship between the consequences of debris levels with mechanical and chemical processes involved in orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Marini et al indicated the importance of repeated oral hygiene instructions and motivations which were crucial in reducing PI scores at a follow up time of 4 weeks to 20 weeks. 37 Some studies have pointed out that it is difficult to remove the plaque from or around the brackets and other orthodontic appliances completely and that it might be helpful for mechanical plaque control to be supported with chemical plaque control. 38 Listerine, the essential oil containing mouthrinse, is effective especially on the supragingival plaque bacteria.…”
Section: Discussionmentioning
confidence: 99%